ANALISIS KONDISI HABITAT DAN PERAKARAN TUMBUHAN BAWAH PADA DAERAH TERBUKA DAN DI BAWAH TEGAKAN CEMARA UDANG DI PESISIR LEMBUPURWO, KEBUMEN - Winastuti Dwi Atmanto; Hesti Wulan Ndari; Sri Danarto (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Coastal areas with sandy soil structure without trees have high temperature and salinity, strong wind, as well as minimum nutrient content. The limitation of the environment conditions affects the variety of undergrowth. This research aims to figure out the composition, distribution patterns, habitat conditions and rooting from undergrowth species which are found in coastal sandy areas at Lemburpurwo. The research was conducted using line transect method defined by systematic sampling with random start. The observations of undergrowth were carried out on 3 types of treads near from the sea, under and behind Cemara Udang stands. Paths are made perpendicular within approximately 53 m from the shoreline and the distance between lines is 95 m. Each track was divided into segments in the form of 2x2 m2 plots which were laid out diagonally between plots for undergrowth observation. 81 plots were taken, where the size of the area is 72960 m2. Undergrowth plant species were identified, the length and number of roots were measured, environmental conditions and soil quality including pH, DHL, N total content, P and K available were observed. Lembupurwo coastal sandy area consists of 20 species of 13 plant families with 3 types of random distribution pattern and 17 types of clustered distribution pattern. Spinifex littoralis has the longest root as well as the largest number of roots, especially in open areas. The pH values and electrical conductivity below the stands of 6.41; 32,23 µs/cm are lower when compared to locations near the sea. N-total and P available under stands are available 0,03%; 5,05 ppm which is higher than the other two locations.